“You Better Werk, Hunty”: Transformations in drag queen culture in central Kansas - Forester, Jakki (Kansas State University. K-State Libraries, 2015)
This ethnography examines different transformations in drag queen culture in central Kansas, which includes the cities of Junction City, Manhattan, Topeka, and Lawrence. The same performers were followed throughout the various performance locations in different cities. Drag queens define their own identities and explain how and why they identify those ways. A detailed case study of one drag queen provides insight into how this drag queen transforms from one gender presentation to another. Personal transformations of all who assisted with this research is explored as a way to address how drag queen culture both in central Kansas and throughout the United States adhere to, challenge, and transcend hegemonic ideals of femininity. Judith Butler’s theory of gender performativity is applied to further analyze the social construction of gender, ways gender is performed, and how drag queens can never fully achieve hegemonic femininity in their performances. The use of space impacts drag queens through perceptions of power and agency within a performance location, but marginalization and oppression in the larger society. The dichotomy juxtaposes two conflicting narratives next to each other – one of inclusion from the queer community and the other of exclusion from the state of Kansas, as a whole. Mixed methods were used to conduct this research including participant observation, ethnography, informal focus groups, three types of interviewing techniques, and photography among others. This ethnography supports some research that already exists, but looks at a queer community in predominantly rural areas, which is unlike other research about drag communities.
Kirmser Undergraduate Research Award - Individual Non-Freshman, honorable mention
Citation: Forester, J. (2016). “You Better Werk, Hunty”: Transformations in drag queen culture in central Kansas. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Drag; Drag Queens; Drag Queen Culture; Drag Queen Aesthetic; Gender Performativity; Rural Queer